The Growth Pole of Bagre: An Analysis of the Communication System around a National Development Project in the Municipality of Bagre, Province of Boulgou, Central Region of Burkina Faso - COMPAORE, Jérôme; BONKOUNGOU, Joachim; TRAORE, Farid (International Journal of Asian Social Science, 2018)
Bagrépôle is the first growth pole in Burkina Faso. This growth pole combines rainy season crops, breeding, fishing, agriculture, wildlife, tourism and represents a place that attracts domestic and international investors. The present study articulated an analysis of the communication of Bagrépôle as a project. It is trying to understand the scope of this communication in the construction of a Bagrépôle culture and an internal and external image. It helps to highlight first the role and the place of communication in the implementation of the project and then the communication strategies adopted with a view to the adhesion of the populations and the investors to the Bagrépôle project.